Quantitative Analysis of the Bacteria in Blepharitis With Demodex Infestation - Zhu, Minyi; Cheng, Chao; Yi, Haisu; Lin, Liping; Wu, Kaili (Frontiers in Microbiology, 2018)
.Bacterial infection or Demodex infestation has been reported to contribute to chronic blepharitis. The association between Demodex mites and bacterial flora in this disease remains to be elucidated. Fifty-six consecutive patients diagnosed with chronic blepharitis and 46 healthy volunteers were recruited for this study. Using specimens of 3 epilated eyelashes and lid margin swabs, Demodex were identified microscopically and bacteria were determined by cultures, followed by colony counting and mass spectrometry. We found 191 Demodex mites, 161 D. folliculorum and 30 D. brevis, in 45 patients. Correspondingly, 101 Demodex, 63 D. folliculorum and 38 D. brevis, were found in 21 controls (p<0.05, both). Bacterial culture-positivity was obtained in samples (eyelashes, lid margins or both) from 54 patients and in eyelashes from 37 controls. The total colony counts and the incidences and colony counts of P. acnes and S. aureus from patients’ eyelashes were significantly higher than that of the controls. Furthermore, bacterial colony counts in blepharitis patients’ eyelashes with D. folliculorum were higher than that of controls with D. folliculorum (p<0.01). Similarly, P. acnes colonies increased significantly in patients’ eyelashes with D. folliculorum (p<0.05). These results suggest that D. folliculorum and P. acnes have a role in the occurrence of the chronic blepharitis. Further studies are required to reveal the relationship between these two organisms in blepharitis.